Estimating the safe mud weight window for drilling operations through pre-stack seismic inversion, a case study in one of the Southwestern Iran oil fields - Mohammad Sadegh Mahmoudian; Yousef Shiri; Ahmad Vaezian (Journal of Petroleum Exploration and Production Technology)
Abstract One of the paramount parameters in the drilling industry is the determination of the safe drilling mud window. Incorrect specification of this parameter can lead to significant hazards such as blowouts, loss of personnel, and substantial costs. The primary objective of this study was to establish a safe mud window using pre-stack seismic inversion and wire-line logs, check shots, and geological data in one of the Southwestern Iran oil fields. Seismic inversion is based on the principle that any physical change in formation, such as porosity or fluid content, affects seismic wave properties. It is used for accurate pore pressure prediction before drilling commences for safe and efficient drilling operations. The pre-stack seismic inversion is conducted by constructing a velocity model and utilizing angle gather aggregation, statistical wavelet extraction, and initial model creation. Seismic inversion analysis revealed that the studied sandstone reservoir layer, known as the Ghar formation, possesses lower P-wave or S-wave acoustic impedance (P-/S-AI) and density compared to adjacent layers, likely due to the presence of porosity and potentially intra-formational fluids. Through seismic inversion and acquisition of AI and density, the pore pressure cube was estimated using a modified Bowers’ relationship. In modified Bowers’ relationship, constants and coefficients are modified based on the observed AI and pore pressure in the wells. The correlation between the estimated pore pressure and the measured pore pressure (RFT, Repeat Formation Tester) in two validation wells, X-01 and X-06, was approximately 0.88 and 0.90, respectively, indicating appropriate prediction results. Examination and assessment of the estimated pore pressure revealed a layer with relatively high pressure compared to neighboring layers, which, according to regional geological reports, was precisely the sandstone Ghar reservoir. Ultimately, after evaluation of pore pressure, drilling mud weight, and formation fracture pressure, the safe drilling mud weight was approximately 200 to 300 (psi) greater than the pore pressure. This study allows for a drilling operation with reduced risk, enhanced safety, and lower costs.